Modified techniques in quantification of intracellular Listeria monocytogenes in vitro infection - Thanh Thao, Tran; Thi Ha, Nguyen (Vietnam Journal of Biotechnology, 2020)
The demand for reliable methods for the quantification of intracellular bacteria is growing. Among modern methods such as PCR and flow cytometry, traditional methods including colony forming unit assay and immune-fluorescence are still the two most commonly techniques worldwide. In colony forming unit assay, there are variations among publications, making data results inconsistent across studies. The aim of this paper is to evaluate available techniques and develop improved protocols for the quantification of intracellular Listeria monocytogenes (LM) in vitro infection assay. This study has suggested different uptake time for phagocytic and non-phagocytic cells. Specifically, uptake time was determined at 0.5 hour after infection for RAW264.7 macrophages and 2 hours for L929 fibroblast host cells. To efficiently remove extracellular bacteria during infection period, gentamicin at high and low concentrations was used during the infection assay. High concentration of gentamicin was used to kill extracellular bacteria while low concentration of gentamicin was used to prevent secondary infection of host cells during the infection period. To obtain a more accurate number of alive LM from a large scale experiment, phosphate-buffered saline/PBS should be used rather than mili-Q (mQ) water to lyse the host cell as mQ water can kill additional bacteria unexpectedly. In immune-fluorescence, LM can be visualized by using either the LM expressing green fluorescence protein (GFP) or antibody against LM. To observed GFP signal, cells should be fixed with paraformaldehyde as methanol will rapidly dim the GFP signal. Findings from this study will benefit researchers engaged in both basic cell biology and infectious diseases.